Body roundness index as a novel marker of periodontitis in US adults - Jun Fang; Minghua Wang; Yanni Sun; Xunxia Wang; Ruichun Wang (Medicine, 2026)
This study aimed to investigate the association between the Body Roundness Index (BRI) and periodontitis (PD) in U.S. adults. Data from 10,790 participants in the 2009–2014 National Health and Nutrition Examination Survey (NHANES) were analyzed. Propensity score matching (PSM, 1:1) balanced baseline characteristics. Logistic regression was used to assess the association between BRI and periodontitis, with BRI modeled as both a continuous and a categorical variable. All subsequent statistical analyses were performed in the matched cohort. Extreme Gradient Boosting (XGBoost) combined with SHapley Additive exPlanations (SHAP) was used to rank predictor importance. Restricted cubic spline (RCS) regression explored nonlinear associations. Subgroup and sensitivity analyses were conducted to examine heterogeneity and test the robustness of the findings. After PSM on age, sex, family income-to-poverty ratio, and race/ethnicity, the BRI index for the PD group (5.34 ± 2.16) was significantly higher than that of the control group (5.07 ± 2.12) ( P < .001). Univariate analysis identified significant factors ( P < .05), and variables with a VIF > 4 were excluded. After adjusting for various factors, BRI was included as a continuous variable, with an odds ratio (OR) of 1.053 (95% CI: 1.016–1.092, P = .0051), indicating that a higher BRI was independently linked to increased odds of PD. Quartile analysis showed an increasing trend in PD occurrence from Q1 to Q4 (Q4 vs Q1, OR: 1.299, 95% CI: 1.047–1.612, P = .0175). The XGBoost model identified BRI as a key variable influencing PD, and cubic spline analysis showed that the odds of PD increased with higher BRI values. Subgroup analysis confirmed this independent association between BRI and PD across various patient groups. BRI is positively and nonlinearly associated with PD, with varying association strength across subgroups. Higher BRI is independently linked to increased odds of periodontitis, and BRI may act as a practical anthropometric marker for stratifying population periodontitis risk.